EFFICACY OF METHOTREXATE ALONE OR WITH LOW-DOSE PREDNISONE IN ALOPECIA AREATA TOTALIS - MUGHAL , H; ABDULLAH , MH; JAMIL , A; MALIK , A; RASHEED , S; KHATOON , F (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to evaluate the efficacy of methotrexate alone or in combination with low-dose prednisone in treating alopecia areata totalis. A randomized controlled trial was conducted among 100 patients diagnosed with alopecia areata totalis. Participants were randomly assigned to two treatment groups: Group A received methotrexate alone, and Group B received methotrexate in combination with low-dose prednisone. The primary outcome measure was the proportion of patients achieving hair regrowth at the end of the treatment period. Secondary outcomes included the time of hair regrowth, the duration of treatment response, and adverse events. Of the 100 patients, 50 were assigned to Group A and 50 to Group B. The study findings revealed that both treatment regimens, methotrexate alone and methotrexate with low-dose prednisone, showed efficacy in promoting hair regrowth in patients with alopecia areata totalis. In Group A, 30 patients (60%) achieved hair regrowth, while in Group B, 40 (80%) achieved hair regrowth. The combination therapy group demonstrated a higher proportion of patients achieving hair regrowth than the methotrexate-alone group. The time for hair regrowth was also shorter in the combination therapy group compared to the methotrexate alone group. Adverse events were minimal and comparable between the two groups. The results of this study suggest that both methotrexate alone and methotrexate in combination with low-dose prednisone are effective treatment options for alopecia areata totalis. The combination therapy showed superior efficacy in achieving hair regrowth and reducing the time to regrowth compared to methotrexate alone. The findings support the use of combination therapy as a potential treatment approach for patients with alopecia areata totalis. However, further research with a larger sample size is warranted to validate these results and establish the optimal dosing and long-term safety of combination therapy in this patient population.